A software defined vehicular network using cooperative intelligent transport system messages - Dias, Duarte Rocha (2021)
The increasing need for smarter means of transportation has brought a greater focus on Vehicular Ad-Hoc Network (VANET)s. VANETs are characterized by frequent topology changes due to high node mobility and most of the existing network protocols for mobility management are not well prepared for constant horizontal handovers. More recently, with the appearance of SDN, new solutions have emerged. The advantages of SDN, such as its exibility and programmability, made it possible to create solutions with lower complexity. This dissertation presents a solution that aims to improve the existing SDN solution, adding elements already present in the ITS universe. The use of C-ITS messages in the SDN universe allows the controller to have a deeper view of the topology state, being able to know where each OBU is located at any time. This global view gives the controller proactiveness, anticipating handovers even before they happen. The prediction of handovers allows the reduction of delays and thus improves the user experience. To evaluate the proposed solution, two types of environments were considered, laboratory and city. For each environment, setups, scenarios and use cases were defined with different characteristics and requirements. The results obtained confirm the correct operation of the solution. When comparing the results of the proposed solution with an existing one, that do not explore the benefits of the ITS universe, we can see an almost zero packet loss rate and a reduction in the average delay.